On the road with Bob Hope and Bing Crosby [videorecording (DVD)] - Schertzinger, Victor; Butler, David, 1894-1979; Walker, Hal, 1896-1972; Crosby, Bing, 1903-1977; Hope, Bob, 1903-2003; Lamour, Dorothy, 1914-1996; Hartman, Don, 1900-1958; Butler, Frank, 1890-1967 (Universal Studios, 2004)
Road to Singapore: "When young shipping mogul Josh Mallon comes too close to getting hitched, he and best buddy Ace Lannigan flee to the farthest point they can find on the map, Singapore."--Container.